2013
DOI: 10.1177/0960327113489050
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of the environmental toxicant benzo(a)pyrene by subcellular fractions of human ovary

Abstract: Knowledge of the ability of the female reproductive system to metabolize environmental chemicals is critical not only from the standpoint of toxicity but also from infertility risk assessment. Benzo( a)pyrene (BaP) is a toxicant that is released into the environment from automobile exhausts, cigarette smoke, burning of refuse, industrial emissions, and hazardous waste sites. In exposed animals, BaP becomes activated to reactive metabolites that interfere with target organ function and as a consequence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 49 publications
0
16
0
Order By: Relevance
“…Benzo(a)pyrene (BaP) is a well-known PAH that can generate reactive oxygen species and create BP diol-epoxide-DNA adducts (BPDE) [66]. BaP exposure can come from automobile exhaust and cigarette smoke [67]. Human exposures to BaP range from 8.4 to 17 µg/person/day through the diet (Ramesh et al, 2011).…”
Section: Polycyclic Aromatic Hydrocarbonsmentioning
confidence: 99%
See 2 more Smart Citations
“…Benzo(a)pyrene (BaP) is a well-known PAH that can generate reactive oxygen species and create BP diol-epoxide-DNA adducts (BPDE) [66]. BaP exposure can come from automobile exhaust and cigarette smoke [67]. Human exposures to BaP range from 8.4 to 17 µg/person/day through the diet (Ramesh et al, 2011).…”
Section: Polycyclic Aromatic Hydrocarbonsmentioning
confidence: 99%
“…Human subcellular ovary samples (n = 8) were incubated with two doses of BaP, 1 µM or 3 µM, in order to measure BaP ovarian toxicity [67]. Ovary samples were obtained from women who underwent operations to remove uterine tumors [67].…”
Section: Female-specific Responsesmentioning
confidence: 99%
See 1 more Smart Citation
“…BaP exposure could alter the steroid balance in females (29)(30)(31), especially the expression of ovarian estrogen receptor (30). It has also been shown that BaP is associated with premature ovarian failure, through the rapid depletion of the primordial follicle pool (32)(33)(34)(35), and causes decreased rates of conception in women who seek in vitro fertilization (36,37). In addition, BaP metabolites impair follicle growth and cause increased primordial follicle activation (38) and follicle atresia in vitro through the induction of apoptosis (39)(40)(41)(42).…”
mentioning
confidence: 99%
“…The metabolites are activated to electrophilic intermediates capable of covalent binding to cellular macromolecules such as DNA, RNA or proteins, which subsequently causes deleterious effects in susceptible tissues. (Ling et al, 2004;Rekhadevi et al, 2014).…”
Section: Introductionmentioning
confidence: 99%